The Influence Of Hedonic Lifestyle, Influencer, And Perceived Risk On Impulsive Buying In Social Commerce - Saeed Ahmed Saeed Al Asrani; Yessy Artanti; Sri Setyo Iriani (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
This study aims to determine the influence of Hedonic Lifestyle, Influencer, and Perceived Risk on Impulsive Buying in Social Commerce. This study uses a quantitative explanatory approach, where data were collected through the distribution of questionnaires to 110 respondents and analyzed using multiple linear regression. The results of this study show that Hedonic Lifestyle, Influencer, and Perceived Risk have an effect on Impulsive Buying in Social Commerce. These findings indicate that Hedonic Lifestyles, Influencers, and Perceived Risk can increase Impulsive Buying in Social Commerce, especially among Gen Z who tend to be more responsive to Social Commerce and actively use social media.